Canagliflozin alleviates valproic acid-induced autism in rat pups: Role of PTEN/PDK/PPAR-γ signaling pathways - Elgamal, Mariam A.; Khodeer, Dina M.; Abdel-Wahab, Basel A.; Ibrahim, Ibrahim Abdel Aziz; Alzahrani, Abdullah R.; Moustafa, Yasser M.; Ali, Azza A.; El-Sayed, Norhan M. (Frontiers in Pharmacology, 2023)
Autism is a complex, multifactorial and one of the fastest growing neurodevelopmental disorders. Canagliflozin (Cana) is an antidiabetic drug that exhibited neuroprotective property in various neurodegenerative syndromes. This study investigated the possible protective effect of Cana against the valproic acid (VPA)-induction model of autism.VPA was injected subcutaneously (SC) into the pups at a dose of 300 mg/kg, twice daily on a postnatal day-2 (PD-2), PD-3, and once on PD-4 to induce autism-like syndrome. Graded doses of Cana were administered (5, 7.5 or 10 mg/kg, P.O.) starting from the first day of VPA injection and continued for 21 days. At the end of the experiment, behavioural tests and histopathological alterations were assessed. In addition, the gene expression of peroxisome proliferator-activated receptor γ (PPAR γ), lactate dehydrogenase A (LDHA), pyruvate dehydrogenase kinase (PDK), c-Myc with protein expression of glucose transporter-1 (GLUT-1), phosphatase and tensin homolog (PTEN) and level of acetylcholine (ACh) were determined. Treatment with Cana significantly counteracted the histopathological changes in the cerebellum and cerebrum tissues of the brain induced by VPA. Cana improved sociability and social preference, enhanced stereotypic behaviours, and decreased hyperlocomotion activity. In addition to its significant effect on canonical Wnt/β-Catenin pathway via the down-regulation of gene expression of LDHA, PDK, c-Myc, protein expression of GLUT, and elevating gene expression of PPAR-γ, protein expression of PTEN and increasing the ACh levels in brain tissues. The current study confirmed the ameliorating effect of Cana against neurochemical and behavioural alterations in the VPA-induction model of autism in rats.